2009
DOI: 10.1103/physrevlett.102.096405
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Storage in a Nanoscale Aharonov-Bohm Ring with Electric Field Tuning

Abstract: We study analytically the optical properties of a simple model for an electron-hole pair on a ring subjected to perpendicular magnetic flux and in-plane electric field. We show how to tune this excitonic system from optically active to optically dark as a function of these external fields. Our results offer a simple mechanism for exciton storage and readout.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 216 publications
(335 reference statements)
1
50
0
Order By: Relevance
“…An in-plane electric field could possibly increase the polarization of an exciton and hence, the visibility of this exciton AB effect. 18 The observation of such effect is not only of fundamental interest, Fischer et al 19,20 suggested recently that the exciton AB effect in a quantum ring can be dynamically controlled by a combination of magnetic and electric fields, a new proposal to trap light.…”
Section: Introductionmentioning
confidence: 99%
“…An in-plane electric field could possibly increase the polarization of an exciton and hence, the visibility of this exciton AB effect. 18 The observation of such effect is not only of fundamental interest, Fischer et al 19,20 suggested recently that the exciton AB effect in a quantum ring can be dynamically controlled by a combination of magnetic and electric fields, a new proposal to trap light.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding eigenfunctions can be determined exactly and the exciton energy obtained from a set of transcendental equations, as reported in Ref. 12.…”
mentioning
confidence: 99%
“…To formulate a consistent picture of correlation between AB interference and e − h interaction, we have used a simplified model according to which the two particle Hamiltonian of the e − h pair interacting by means of a contact potential in a ring of radius R and zero width threaded by a magnetic flux Φ = BπR 2 is described by [12] …”
mentioning
confidence: 99%
“…A short-range interaction between the electron and the hole has been investigated for one-dimensional (1D) rings, 13,14,18,19 where also the effect of an external electric field can be included. 20 Intermediate models assume twodimensional (2D) rings with narrow width under harmonic confinement and Coulomb-like interaction potentials between the electron and the hole, 21,22 or radial-polarized excitons when electrons and holes move in different circles. [23][24][25] The excitonic AB effect in 2D rings has been studied in models with harmonic 26 and geometric 15,27,28 confining potential or using a 2D attractive annular Hubbard model.…”
Section: Introductionmentioning
confidence: 99%